2021
DOI: 10.1177/02184923211019530
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative hypothermia on outcomes after off-pump coronary artery bypass grafting

Abstract: Background Even though the physiological derangements caused by hypothermia are well described, there is no consensus about its impact on postoperative outcomes. The aim of this study is to assess the effect of postoperative hypothermia on outcomes after off-pump coronary artery bypass surgery. Methods A total of 1979 patients undergoing isolated off-pump coronary artery bypass surgery in a single center in the period 2007–2018 were classified according to their axillary temperature measurement at intensive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Likewise, Nam et al [ 20 ] reported that the all-cause mortality of moderate-to-severe hypothermia was more than two times of that in normothermia for off-pump CABG patients and even mild hypothermia (no less than 35.5℃) was found an unsatisfied outcome during the follow-up of 47 months. However, another study that enrolled isolated off-pump CABG patients showed no statistically difference for in-hospital mortality between hypothermia group and normothermia group neither before nor after propensity score matching, while a distinction in postoperative transfusion of red cell concentrates, duration of intubation and ICU stay [ 15 ]. Unexpectedly, there was a higher rate of in-hospital mortality in the normothermia group than in the hypothermia group after pairing, though this difference was not statistically significant ( P = 0.975 vs. P = 0.244).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Nam et al [ 20 ] reported that the all-cause mortality of moderate-to-severe hypothermia was more than two times of that in normothermia for off-pump CABG patients and even mild hypothermia (no less than 35.5℃) was found an unsatisfied outcome during the follow-up of 47 months. However, another study that enrolled isolated off-pump CABG patients showed no statistically difference for in-hospital mortality between hypothermia group and normothermia group neither before nor after propensity score matching, while a distinction in postoperative transfusion of red cell concentrates, duration of intubation and ICU stay [ 15 ]. Unexpectedly, there was a higher rate of in-hospital mortality in the normothermia group than in the hypothermia group after pairing, though this difference was not statistically significant ( P = 0.975 vs. P = 0.244).…”
Section: Discussionmentioning
confidence: 99%
“…Whether temperature abnormalities have an influence on CHD patients remains unknown yet, so we hypothesized low body temperature was linked with worse outcome based on similar investigations aiming at patients undergoing coronary artery bypass grafting (CABG) [ 14 , 15 ] and other cardiac surgeries [ 16 ]. And we tested this in the Medical Information Mart for Intensive Care (MIMIC)-IV database in a pre-specified manner.…”
Section: Introductionmentioning
confidence: 99%
“…For the primary outcome, we conducted univariate logistic regression analyses on variables known to be risk factors for postoperative hypothermia, including age, operation duration [ 18 ], body mass index [ 19 ], intraoperative fluid, intraoperative bleeding and transfusion [ 20 ], as well as surgeries performed in the Hybrid OR. Age and operation duration were categorized based on the median values of the entire dataset, while body mass index, intraoperative fluid, and intraoperative bleeding were categorized based on the 25th and 75th percentiles; intraoperative transfusion was categorized by the number of transfused packs.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Physiological derangements caused by hypothermia and its impact on postoperative outcomes are well described (increased incidence of coagulopathy, bleeding and wound infections, a greater risk of cardiovascular complications, a longer intensive care unit stay, and increased costs). [5][6][7] On the other hand, hyperthermia during cardiac surgery has been associated with increased risk of postoperative neurocognitive dysfunction and kidney damage, especially when temperatures exceeding 37°C during rewarming. [8][9][10][11][12] Hyperthermia, even if mild, aggravates ischemic neuronal injury and accelerates neuronal death.…”
Section: Introductionmentioning
confidence: 99%